Specific Features of Police Management Compared to General Management - Talijan, Momčilo; Ristović, Svetlana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2007)
The paper opens with the most general findings on management in general and moves on to convey the results of both empirical and theoretical research of the authors concerning jurisdiction (powers) and subjects (executives) of police management, its levels and types, as well as factors that influence the choice of strategy and development of adequate styles and forms of police management. The findings related to management in general and police management in particular have been compared in order to establish possible similarities and differences between these two types of management.